2018
DOI: 10.1016/j.pestbp.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of oxime-assisted reactivation of human, Guinea pig, and rat acetylcholinesterase inhibited by the organophosphorus pesticide metabolite phorate oxon (PHO)

Abstract: Phorate is a highly toxic agricultural pesticide currently in use throughout the world. Like many other organophosphorus (OP) pesticides, the primary mechanism of the acute toxicity of phorate is acetylcholinesterase (AChE) inhibition mediated by its bioactivated oxon metabolite. AChE reactivation is a critical aspect in the treatment of acute OP intoxication. Unfortunately, very little is currently known about the capacity of various oximes to rescue phorate oxon (PHO)-inhibited AChE. To help fill this knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, organophosphorus pesticide (OP) disrupts many other neurotransmitters, and some of these are entailed in mood regulation, such as serotonin. This could clarify the connection between pesticide exposure and mood disorders seen in earlier studies [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, organophosphorus pesticide (OP) disrupts many other neurotransmitters, and some of these are entailed in mood regulation, such as serotonin. This could clarify the connection between pesticide exposure and mood disorders seen in earlier studies [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 52%
“…Recent studies have highlighted that long-term low/moderate exposure to OP could be correlated with impaired neurobehavioral function or other neurological effects [ 32 , 33 ], while the studies have reported higher suicide rates among farmers who used it than in the general population [ 34 , 35 ]. Other investigations on the chronic toxicity of OP have shown kidney damage in animal models mediated by several mechanisms such as damage to the cell membrane and proteins through oxidative stress induced by the generation of free oxygen radicals, functional disturbances related to plasma membrane injury, cellular DNA damage, and activation of apoptosis-related p53 [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. In the present study, we report a case of suicide carried out through the high ingestion of phorate of an agricultural worker exposed to phorate, at low doses, for several years.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, [ 18 F]‐VXS was selected as a tracer to develop a quantitative PET imaging platform to measure available/functional AChE in live tissues following OP exposure and after intervention with oximes. POX was chosen as the OP challenge agent since it is a potent anticholinesterase inhibitor, affords a predictable toxicological profile, and the diethylphosphoryl–AChE adduct formed by POX (or related diethoxy phosphorylating agents, such as phorate 44 ) undergoes reactivation by oximes and does not age in the hours following AChE inhibition 45 …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, dealkylation of a phosphorus ester can occur via aging (loss of R; k 4 ), thereby sustaining the AChE blockade , (Figure ). Aged OP-AChE adducts are concerning because they are recalcitrant to reactivation even with oxime antidotes. …”
Section: Introductionmentioning
confidence: 99%